2013
DOI: 10.1021/om4009058
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Intramolecular Hydroamination of Allenes using Mononuclear Gold Catalysts

Abstract: The intramolecular gold-catalyzed asymmetric hydroamination of allenes was studied by screening a series of mononuclear gold(I) and -(III) complexes in combination with silver salts. Among the various chiral monophosphine and diaminocarbene ligands tried, the best catalysts arose from mononuclear gold(I) complexes synthesized from BINOL-based phosphoramidite ligands. The latest were improved by addition of bulky substituents at specific positions of the BINOL scaffold. The resulting gold(I) complexes were comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 185 publications
0
22
0
Order By: Relevance
“…Along our studies on gold‐catalysed hydroamination reactions, we noticed a positive silver effect for binuclear gold(I) catalysts but none for mononuclear ones . Indeed, a phosphoramidite mononuclear gold(I) cationic species led to an unchanged reaction outcome while removing AgCl by filtration through Celite or a PTFE filter prior to the catalysis.…”
Section: Introductionmentioning
confidence: 86%
“…Along our studies on gold‐catalysed hydroamination reactions, we noticed a positive silver effect for binuclear gold(I) catalysts but none for mononuclear ones . Indeed, a phosphoramidite mononuclear gold(I) cationic species led to an unchanged reaction outcome while removing AgCl by filtration through Celite or a PTFE filter prior to the catalysis.…”
Section: Introductionmentioning
confidence: 86%
“…Only two articles devoted to this subject have appeared, reported independently by Shi [82] and Agbossou-Niedercorn [115,118] (Scheme 32). Unfortunately, higher temperature was needed to reach moderate yield, which was responsible for low enantioselectivity.…”
Section: Furan Pyrrolidine and Indanone Derivativesmentioning
confidence: 99%
“…In contrast to gold(I) complexes, the synthetic efforts leading to their gold(III) counterparts have met with little success to date and there have only been two reports devoted to chiral gold(III) complexes. The seminal work of Michon and Agbossou-Niedercorn [115,118] proved that chiral Scheme 45. Intermolecular asymmetric hydroazidation and hydroamination of allenes.…”
Section: The Synthesis Of Gold(iii) Complexesmentioning
confidence: 99%
“…In addition to the modularity provided by a convergent catalyst synthesis, this system was attractive as only one gold atom is required to accomplish previously published transformations with similar levels of conversion and enantioselectivity. Michon et al have also shown BINOL-based phosphoramidite catalysts are relatively competent at forming enantioenriched pyrrolidines [70]. In addition to these conventional approaches to hydrofunctionalization of allenes, Lipshutz et al have demonstrated the ability to synthesize enantioenriched lactones inside a PEGylated micelle using water as the bulk solution [71].…”
Section: Intramolecular Cyclizationsmentioning
confidence: 99%